The use of supplements and performance and image enhancing drugs in fitness settings: A exploratory cross‐sectional investigation in the United Kingdom. (May 2017) - Mooney, Roisin; Simonato, Pierluigi; Ruparelia, Risha; Roman‐Urrestarazu, Andres; Martinotti, Giovanni; Corazza, Ornella
Abstract: Objective: The strive for perfection is prevalent in the fitness industry. This study aimed to explore the use of products to enhance performance alongside exposure to exercise addiction, appearance anxiety and self‐esteem in fitness settings. Methods: An online survey was prepared and piloted before wider dissemination in fitness clubs via snowballing and selected mailing lists. A list of commonly used products, including Performance and Image Enhancing Drugs (PIEDs) was provided. Exercise addiction (Exercise Addiction Inventory; EAI), anxiety levels (Appearance Anxiety Inventory; AAI) and their self‐esteem (Rosenberg's Self‐Esteem Scale; RSE) were also measured. Results: 377 questionnaires were completed. A significant number of participants declared the use products either to lose weight (16%) or to reach their fitness goals (41%). The Internet played a major role in both the supply of information and the provision of the enhancement products (33.7%) and side effects were reported (10.5%). Only a limited number of participants sought a medical opinion about taking products (5.1%). EAI scores were high (m=20.02 ± 4.1), AAI (m=15.98 ± 4.8) showed an intermediate level of anxiety, while self‐esteem was low (RSE m=12.59 ± 2.2). Conclusion: This pilot study identified the emergence of a new drug trend in fitness settings and showed a potential relationship to exercise addiction, anxiety disorders and low self‐esteem. The Internet played a crucial role in disseminating often untested products, including PIEDs without medical supervision and unwanted side‐effects were reported. More studies in the field are required in order to safeguard public health and inform policy making.